2012
DOI: 10.1093/icvts/ivs076
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and predictors of prolonged ventilation in patients undergoing elective coronary surgery

Abstract: OBJECTIVES Despite the seriousness of prolonged mechanical ventilation (PMV) as a postoperative complication, previously proposed risk prediction models were met with limited success. The purpose of this study was to identify perioperative variables associated with PMV in elective primary coronary bypass surgery. PMV was defined as the need for intubation and mechanical ventilation for >72 h, after completion of the operation. METHODS Between April 1997 and September 2010, 10 ,977 consecutive patients were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
3
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 22 publications
4
45
3
4
Order By: Relevance
“…Compared with the numerous studies on this subject, [1][2][3]29 the patient number may seem low to make many inferences from this study. However, the authors believe that the analysis of a tertiary teaching hospital with a high proportion of PMV patients with cardiac etiology may be interesting to others.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Compared with the numerous studies on this subject, [1][2][3]29 the patient number may seem low to make many inferences from this study. However, the authors believe that the analysis of a tertiary teaching hospital with a high proportion of PMV patients with cardiac etiology may be interesting to others.…”
Section: Discussionmentioning
confidence: 75%
“…Based on the previous reports, lower early and midterm survival are apparent in patients with PMV. 2,3 The aforementioned studies reported series of patients with high pulmonary risk in PMV. However, there still may be a significant number of patients who require PMV due to cardiac causes.…”
mentioning
confidence: 99%
“…Obesity has been suggested as an important risk factor in cardiac surgery, but in recent years acceptable results have been documented which indicated the influence of the improvements in this field. Yet, there is still controversy (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The data on the prolonged mechanical ventilation in obese patients are conflicting. Saleh et al [29] studied the risk factors of prolonged ventilation in patients undergoing CABG and they found that BMI > 35 kg/m 2 was a predictor of prolonged respiratory support. Similar results were observed by Gurbuz et al [8].…”
Section: Discussionmentioning
confidence: 99%